China at the threshold of a market economy - Bell, Michael W.; Khor, Hoe Ee; Kochhar, Kalpana; Ma, Jun; N'guiamba, S. (Simon); Lall, Rajiv B. (Washington, DC : International Monetary Fund, 1993)
This occasional paper undertakes a comprehensive review of China's reform experience since 1978. It identifies special conditions that may have affected China's capacity to implement reforms and draws implications for the direction of China's future reform strategy.
"September 1993."
Keywords: China -- Economic policy -- 1976-2000; China -- Economic conditions -- 1976-2000